ANALISIS IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY EDU VISIT PT GARUDA MAINTENANCE FACILITY AEROASIA, TBK - Sella Lovityo Aulia; Chrisentia Flavia Dwianjani; rubiyanto rubiyanto (Prodi Ilmu Komunikasi Universitas Putera Batam, 2020)
PT Garuda Maintenance Facility, AeroAsia, Tbk (GMF) is a state-owned company engaged in the aircraft maintenance and repair service industry in Indonesia, or Maintenance, Repair, and Overhaul abbreviated as MRO. One of the activities carried out is Corporate Social Responsibility / CSR, which is named ‘edu visit’. Since 2002, edu visits have provided opportunities for the public, especially students and university students to visit GMF, who want to know about aerospace. The purpose of this study is to provide an overview to readers about the activity of edu visits, the constraints and solutions undertaken. The method used is qualitative with a descriptive approach. The data were obtained through interviews, observation, and documentation. Researchers use Legitimacy Theory and the concept of CSR to answer the research objectives. The results can be illustrated that the edu visit activity has been carried out by the company implementing the legitimacy effectiveness and the right CSR concept. External and internal obstacles can be resolved through communication and coordination with other divisions within the company. Keyword: Corporate Social Responsibility, Legitimacy Theory